Assessment of the Status of Rooftop Garden, Its Diversity, and Determinants of Urban Green Roofs in Nepal. (6th June 2022) - Rawal, Sara; Thapa, Sandesh
Abstract : In recent days, the practice of adopting rooftop garden can be seen in urban areas of developing countries, but a successful adoption of well-equipped green roofs is still lacking and is limited to open farms. To fulfill the gaps in urban agriculture in determining diversity status and socioeconomic factors affecting the adoption of RTG, this study was conducted. The survey was conducted from February 3 to April 6, 2021, where a total of 116 respondents were selected randomly from Morang and Sunsari districts. The rooftop adopters had 30.5% and 33.2% of the roofs under farming in Morang and Sunsari, respectively, having the size of the roof of rooftop adopters significantly larger than nonadopters. A binary logit model was used to determine the factor affecting the adoption of RTG where age, gender, schooling year, training, and farming experience have a significant effect on the adoption of RTG. Locally available material was given preference under farming and nutritionally important 50 species were reported with tests of the daily food requirement of the respondents. The diversity indices suggest that ornamental plant diversity is more followed by vegetables. Though, adopters are continuing the garden but have reported that lack of proper policy and ineffective management makes it difficult to protect the life of roof. Concludingly, respondents and other willing people must be provided with training, financial support, and proper extension services as lack of training and extension services are the major problems reported in the study area. Proper policy of rooftop garden is lacking in study area though it is under study in Kathmandu; thus, policy makers and research institution should focus on promoting the rooftop in study area and provide more reliable package for roof protection and garden continuation.